Developing EFL Senior High School Students' Accuract and Fluency in Spoken English by Using Guided Speaking Worksheets - Julian Chandra; Amal Hayati (JAMBI-ENGLISH LANGUAGE TEACHING, 2017)
Developing communicative competence is fundamental framework in the curriculum of teaching spoken English for EFL senior high school students in Indonesian. It is a concept of teaching spoken English which refers to the necessity for the learners to have both accuracy and fluency. Therefore, a form and a meaning -based strategy in teaching spoken English that promote EFL learners’ accuracy and fluency are needed. This research was aimed at finding out whether there was a significant effect of using speaking worksheet towards the students’ accuracy and fluency in teaching spoken English. Quasi-experimental research with pre-test and post-test design was employed. Population was 22 tenth grade of senior high school students of whom 11 each were then randomly assigned as samples in experimental group and in control group. Samples in experimental group received self- teacher made speaking worksheets while samples in control group were not given. Instrument of the research was oral test in which its validity and reliability were determined by content validity and inter-ratercoefficient correlation. Nonparametric analysis with Mann-Whitney U formula was employed to test hypothesis. For fluency in spoken English, it was found that U-calculated (-27) was smaller than U-table(34), while for accuracy it was found that U-observed (-15) was smaller than U-table (34). It means that H0 was rejected and H1 was accepted. It is concluded that there was significant effect of using self-made speaking worksheet towards the students’ accuracy and fluency in teaching spoken English. The findings lead to discussion to their impact on language pedagogy.